1994
DOI: 10.1159/000159063
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hypertensive Deoxycorticosterone-Salt Treatment Accelerates Atherosclerosis Progression in Watanabe Heritable Hyperlipidemic Rabbit

Abstract: Epidemiological studies have indicated that hypertension enhances the development of atherosclerosis in patients with lipid disorders. However, it was still unclear whether this promoting effect resulted only from hemodynamic changes or whether part of it was mediated by humoral or neurogenic factors independent of blood pressure alteration. The aim of this study was to determine whether mineralocorticoids, which are known to be involved in the pathogenesis of hypertension, could be implicated in the atheroscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Raven et al have shown that, in a small cohort of mentally depressed human subjects, metyrapone treatment was associated with a striking >5-fold increase in the urinary output of 11-deoxycortisol (deoxycortisol) metabolites [ 21 ]. Treatment with deoxycorticosterone stimulates atherogenesis in Watanabe heritable hyperlipidemic rabbits [ 22 ] as well as in hyperlipidemic apolipoprotein E knockout mice [ 23 ]. Lother et al have shown that deoxycorticosterone executes its pathological vascular effects through activation of the mineralocorticoid receptor (MR) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Raven et al have shown that, in a small cohort of mentally depressed human subjects, metyrapone treatment was associated with a striking >5-fold increase in the urinary output of 11-deoxycortisol (deoxycortisol) metabolites [ 21 ]. Treatment with deoxycorticosterone stimulates atherogenesis in Watanabe heritable hyperlipidemic rabbits [ 22 ] as well as in hyperlipidemic apolipoprotein E knockout mice [ 23 ]. Lother et al have shown that deoxycorticosterone executes its pathological vascular effects through activation of the mineralocorticoid receptor (MR) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%